How can luxury interior design brands grow through digital- the case of covet group and the launch of home´society platform: the analysis of made-in Portugal brand positioning for home´society - Gouveia, Maria Jorge De Albuquerque (2021)
This project examinesthe viabilityof a proposed online marketplace fora Portuguese Interior Design company. The proposed paper consists of both a group and an individual part. In the group part, qualitative research was conducted to understand how Professionals and Final Consumers interact and what adherence to the market place would look like .In the individual parts the thesis’ authors individually examined in-depth some implication that arose from the qualitative analysis: (1) which strategy should the marketplace follow, (2)how to engage both targets to the platform, (3)and the relevance of the Made-in Portugal brand within the platform.